Cerebral protection in TAVR – can we do without? Impact on stroke rate, length of hospital stay and 12-month mortality. (14th October 2021) - Dona, C; Koschutnik, M; Nitsche, C; Winter, M P; Mach, M; Andreas, M; Bartko, P; Kammerlander, A; Goliasch, G; Lang, I; Hengstenberg, C; Mascherbauer, J
Abstract: : Stroke associated with transcatheter aortic valve replacement (TAVR) is a potentially devastating complication. Until recently, the Sentinel™ Cerebral Protection System (CPS; Boston Scientific) has been the only commercially available device for mechanical prevention of TAVR-related stroke. However, its effectiveness is still undetermined. Methods: Between January 2019 and August 2020 consecutive patients were randomly assigned to TAVR with or without Sentinel™ in a 1:1 fashion. We defined as primary endpoint clinically detectable cerebrovascular events within 72 hours after TAVR, and as secondary endpoints LOS and 12-month mortality. Logistic and linear regression analyses were used to assess associations of Sentinel™ use with endpoints. Results: Of 411 patients (80±7 y/o, 47.4% female, EuroSCORE II 6.3±5.9%), Sentinel™ was used in 213 (51.8%), with both filters correctly deployed in 189 (46.0%). 20 (4.9%) cerebrovascular events were recorded, 10 (2.4%) of which were disabling strokes. Sentinel™ reduced cerebrovascular events in univariate analysis by 71% (OR 0.29, 95% CI 0.11–0.82; p=0.02) and after multivariate adjustment by 75% (adj. OR 0.25; 95% CI 0.08–0.80; p=0.02). Sentinel™ use was also significantly associated with shorter LOS (8.4±9.6 versus 6.7±6.1 days; p=0.03) and lower 12-month all-cause mortality (15.7% versus 7.5%, p=0.01). Conclusions: In the present prospective all-comers TAVR cohort, Sentinel™ significantly 1) reduced cerebrovascular events, 2) shortened LOS, and 3) improved 12-month survival. These data promote the use of a CPS when implanting TAVR valves. FUNDunding Acknowledgement: Type of funding sources: None.